Design of a cusped field thruster for drag-free flight. (September 2016) - Liu, H.; Chen, P.B.; Sun, Q.Q.; Hu, P.; Meng, Y.C.; Mao, W.; Yu, D.R.
Abstract: Drag-free flight has played a more and more important role in many space missions. The thrust control system is the key unit to achieve drag-free flight by providing a precise compensation for the disturbing force except gravity. The cusped field thruster has shown a significant potential to be capable of the function due to its long life, high efficiency, and simplicity. This paper demonstrates a cusped field thruster's feasibility in drag-free flight based on its instinctive characteristics and describes a detailed design of a cusped field thruster made by Harbin Institute of Technology (HIT). Furthermore, the performance test is conducted, which shows that the cusped field thruster can achieve a continuously variable thrust from 1 to 20 mN with a low noise and high resolution below 650 W, and the specific impulse can achieve 1800 s under a thrust of 18 mN and discharge voltage of 1000 V. The thruster's overall performance indicates that the cusped field thruster is quite capable of achieving drag-free flight. With the further optimization, the cusped field thruster will exhibit a more extensive application value. Highlights: A cusped field thruster for drag-free flight is designed and tested. The feasibility of cusped field thrusters for drag-free flight is demonstrated. The cusped field thruster can adjust thrust from 1 to 20 mN continuously. The cusped field thruster is expected to have a low noise and high resolution.